If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + (8x + 12) = 19x + 10 Reorder the terms: 10x + (12 + 8x) = 19x + 10 Remove parenthesis around (12 + 8x) 10x + 12 + 8x = 19x + 10 Reorder the terms: 12 + 10x + 8x = 19x + 10 Combine like terms: 10x + 8x = 18x 12 + 18x = 19x + 10 Reorder the terms: 12 + 18x = 10 + 19x Solving 12 + 18x = 10 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. 12 + 18x + -19x = 10 + 19x + -19x Combine like terms: 18x + -19x = -1x 12 + -1x = 10 + 19x + -19x Combine like terms: 19x + -19x = 0 12 + -1x = 10 + 0 12 + -1x = 10 Add '-12' to each side of the equation. 12 + -12 + -1x = 10 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 10 + -12 -1x = 10 + -12 Combine like terms: 10 + -12 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 2x+18=4x-2 | | 8x+16=14x-14 | | 7a/2=15 | | 42-0.125Q=10+.075Q | | 2W^2+8W-42-W^2-7W-198=0 | | -2a^2+12b+7=0 | | 6-+8= | | -54/6= | | -12/-4= | | (7x-12)-(7x-11)=1 | | 4--9+-7= | | a/26-5.5v2a=9/13+20a/13+4/13 | | 147-7x=29x+23 | | 0=6x^2+12x-594 | | -11x=-7 | | 602-67x=53xk | | 23/k+1=4 | | 2+x+5/4=x+1 | | -3(x-5)+5(x+7)+22=82 | | 2x+5x=13 | | 160-5x=40x+20 | | 3x+14=-27-7x | | 82-2x=16x+20 | | b^2-11n+24=0 | | 2x+22=12x-88 | | -24-2x=3x+6 | | (x+6)+13=3x+15 | | 7x+16=6x+18 | | 15x-16=(10x)+(4x+1) | | 3-x/4=-1 | | (9x-5)+(5x-1)=13x+7 | | m+2m=105 |